Car ignition system via mobile phone - Karim, Jamilah; Amat, Wan Mohd Arman Bin Wan; Razak, Abdul Hadi Abdul (2009)
SMS text messaging is the most popular and widely used data application in this era for sending text messages from one mobile to another. Short Message Service (SMS) is a communications protocol allowing the interchange of short text messages between mobile telephone devices [7].Short messages can be encoded using a variety of alphabets. The implementation of Car ignition system through mobile phone consists of 2 parts: software design and hardware development. The software part is designed by using Dynamic and loads the program into Rabbit Core Module (RCM3200). The data loaded into RCM3200 will be saving at the memory. The hardware parts are Rabbit Core Module (RCM3200) with Prototyping Board (RCM3100), GSM/GPRS modem: Wavecom 900/1900 MHz Machine-to-Machine (M2M) and bipolar junction transistor (BJT) circuit. The system purpose is to ignite the car engine by using the mobile phone.By sending a text message (SMS) from mobile phone, the system could ignite the engine. The advantage of this system is user could ignite their car engine wherever they parked their car whether near or far distance from the user. The engine will run for 5 minute without unlocks the door.